Develop spinel structure and quantify phase transformation for nickel stabilization in electroplating sludge. (15th July 2021) - Xia, Yunxue; Meng, Fanling; Lv, Zhong; Zhang, Jianshuai; Tang, Yuanyuan; Shih, Kaimin
Graphical abstract: Ni in the electroplating sludge can be incorporated into NiFe2 O4 and NiAl2 O4 spinel structures, when two typical ceramic precursors (α-Fe2 O3 and γ-Al2 O3 ) were used respectively. The transformation ratio of Ni into the either spinel can reach over 99%. The two spinels exhibit superiority in Ni stabilization with leached ratio of <0.06% even after a long-term (20 d) TCLP leaching test. Highlights: NiFe2 O4 /NiAl2 O4 spinels were developed by sintering Ni sludge with α-Fe2 O3 /γ-Al2 O3 . Phase distribution and Ni transformation were quantified with temperature effect. Less than 0.06% of total Ni was leached out even after 20d prolonged leaching. Excellent Ni stabilization was realized at attainable sintering temperatures. Abstract: Nickel-laden electroplating sludge (Ni sludge) has always been a critical concern due to its potential hazards to the environment. This study proposed a strategy to stabilize nickel (Ni) via phase transformation into stable crystal structures through ceramic sintering. The Ni sludge was collected, and then fired with two ceramic precursors (α-Fe2 O3 and γ-Al2 O3 ) within a temperature range of 700–1400 °C for 5 h. After sintering scheme, phase identification was performed on the products, showing the NiFe2 O4 and NiAl2 O4 spinels as predominant Ni-hosting phases respectively in α-Fe2 O3 and γ-Al2 O3 series. Then, the Rietveld refinement was applied to quantify weight fractions of all phases (including crystal and amorphous phases), and the quantification results showed that the weight fractions of NiFe2 O4 or NiAl2 O4 spinels can reach around 87.7% and 83.1%, respectively in 1200 °C sintered products of both series. The transformation ratio (TR) of Ni was calculated as 99.9% and 99.7% accordingly, showing almost complete incorporation of Ni into the spinel structures. With a prolonged leaching procedure, the Ni stabilization effect after sintering was evaluated. The Ni leachability was dramatically decreased with the development of spinel structure under sintering processes, and the Ni leached ratio from the sintered products can reach lower than 0.06% even after 20-d prolonged leaching. Through this study, a promising and quantitative method was proposed for controllable Ni stabilization of the hazardous industrial sludge via developing spinel structures in the sintered products, which may provide a feasible strategy for the treatment and beneficial utilization of heavy metal-laden solid wastes.